Determination of Binary Gas Mixtures by Measuring the Resonance Frequency in a Piezoelectric Tube - Kanchalar Keeratirawee; Peter C. Hauser (Sensors, 2022)
.
Keywords: Advanced MEMS and NEMS Technologies; Gas Sensing Nanomaterials and Sensors; Advanced Chemical Sensor Technologies